KAJIAN USAHA HIDANGAN ISTIMEWA KAMPUNG (HIK) DI KABUPATEN BOYOLALI - Haris Akhmad Affandi; Sudarmadi Sudarmadi (STIE Atma Bhakti, 2019)
This study aimed to determine the effect of capital, long effort, time business, labor, and the distance effort against HIK trader profits in Boyolali. In addition, this study aims to examine whether there is a significant difference between the variable status of the business and location of the business to the HIK trader profits in Boyolali for a month. The data used in this study are primary data analysis tool that is used by multiple linear regression, the two mean difference test independent and different test one-way ANOVA. There is a single dependent variable is profit and seven independent variables is the variable capital, long effort, time effort, the amount of labor, business status, and location of the business. Results of regression with a significance of 10% indicates that the capital, experience, time business, labor, and the distance effort positively affects on traders' profits, while the time of the attempt shows a negative effect on HIK trader profits in Boyolali. From the test results mean difference two independent and one-way ANOVA showed that the status of the business does not have a significant difference to the traders' profits, while the location of the business has a significant difference to the HIK trader profits in Boyolali.The government is expected to provide some capital and licensing, other than that the government must pay attention to equitable regional development, so as to form the center of the new economy will be beneficial to the business continuity HIK stalls.